PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS III SD NEGERI 064971 MEDAN TEMBUNG - Kameilia Wandari; Indah Pratiwi; Roida Siboro (STKIP Subang, 2024)
The aim of this research is to improve student learning outcomes in mathematics learning through a problem based learning model. This type of research is Classroom Action Research (PTK) on the subject of class III students at SD Negeri 064971 Medan Tembung, totaling 13 students. This research consists of two cycles, with stages namely: planning, implementation, observation and reflection. The data collection techniques used were observation sheets and tests. Meanwhile, the data analysis technique uses the average value formula, percentage of learning completeness and observation data. The results of the research show that there is an increase in mathematics learning outcomes by implementing the problem based learning model. The improvement in mathematics learning outcomes can be seen from the data obtained in cycle I and cycle II. In cycle I there were 7 students who completed it with a percentage of 53.84%. In cycle II there were 10 students who completed it with a percentage of 84.61%. So the increase in mathematics learning outcomes from cycle I to cycle II was 30.77%. Similar to the results of these data, it can be concluded that problem-based learning can improve student learning outcomes in mathematics learning in class III at SD Negeri 064971 Medan Tembung.